Effect of Superficially Porous Particles on Chromatographic Analysis Time of Flavonoids - Alfatly , Raid Abdulmehdi; Rasheed, Ashraf Saad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Due to superficial particles and remarkable packing technologies, the HALO-HILIC column outperformed regular porous columns in terms of analysis time. This study analyzes and identifies kaempferol and luteolin flavonoids in natural herbs. A fast, novel chromatographic method combining superficially porous silica particles packed in a column served as the separation tool for hydrophilic interaction liquid chromatography coupled with a UV detection system is being introduced in this work. Flavonoid separation and quantification took six minutes using only superficial porous particles in the HILIC column compared to hours using fully porous particles in the RP columns. The findings demonstrated that the HILIC mode might be utilized to determine kaempferol and luteolin levels in ginkgo plant samples. A commercial HALO-HILIC column was used to create the calibration curve, which had the following specifications: linear range (0.065-35 µgmL-1 for kaempferol and 0.065-9 µgmL-1 for luteolin), RSD% not exceeding 0.54%, the limit of quantification (0.036 µgmL-1 for kaempferol and 0.024 µgmL-1 for luteolin), and limit of determination (0.012 µgmL-1 for kaempferol and 0.008 µgmL-1 for luteolin).